Controlling the Self‐Metalation Rate of Tetraphenylporphyrins on Cu(111) via Cyano Functionalization. Issue 32 (14th June 2018) - Lepper, Michael; Köbl, Julia; Zhang, Liang; Meusel, Manuel; Hölzel, Helen; Lungerich, Dominik; Jux, Norbert; de Siervo, Abner; Meyer, Bernd; Steinrück, Hans‐Peter; Marbach, Hubertus
Abstract: The reaction rate of the self‐metalation of free‐base tetraphenylporphyrins (TPPs) on Cu(111) increases with the number of cyano groups ( n =0, 1, 2, 4) attached at the para positions of the phenyl rings. The findings are based on isothermal scanning tunneling microscopy (STM) measurements. At room temperature, all investigated free‐base TPP derivatives adsorb as individual molecules and are aligned with respect to densely packed Cu substrate rows. Annealing at 400 K leads to the formation of linear dimers and/or multimers via CN‐Cu‐CN bonds, accompanied by self‐metalation of the free‐base porphyrins following a first‐order rate equation. When comparing the non‐cyano‐functionalized and the tetracyano‐functionalized molecules, we find a decrease of the reaction rate by a factor of more than 20, corresponding to an increase of the activation energy from 1.48 to 1.59 eV. Density functional theory (DFT) calculations give insights into the influence of the peripheral electron‐withdrawing cyano groups and explain the experimentally observed effects. Abstract : Put on the brakes ! The yield of the self‐metalation reaction of tetraphenylporphyrins on Cu(111) systematically decreases with an increasing number of cyano substituents ( n =0, 1, 2, 4). This opens up a novel strategy to effectively tweak the reaction.